Late onset Leigh syndrome: about an observation - ahira BARKA-BEDRANE; Djaoued BOUCHENAK-KHELLADI; Cherifa LOUHIBI; Hakim CHIALI (Journal de la Faculté de Médecine d'Oran, 2020)
Leigh Syndrome (LS) is a rare childhood mitochondriopathy characterized by clinical polymorphism. Generally, it begins at the age of 2 years .We report the case of a 13 year old patient, born from on inbred marriage,she resented a significant decrease of visual acuity at the age of 9 years. Towards the age of 13 years, she presented bulbar and walking disorders. The neurological examination found a ppyramidal, an extrapyramidal, a neurogenic syndromes and a kyphoscoliosis. Brain MRI objectified a bilateral and symmetrical hyper signal in the brainstem, the basal ganglia and the periaqueductal region. Brain spectro-MRI found a peak in lactates.